Pengaruh Gaya Kepemimpinan Situasional Kepala Sekolah dan Literasi Digital Terhadap Kompetensi Pedagogik Guru SD Negeri di Kecamatan Kunduran - Ela Sofiati; Soedjono Soedjono; Harto Nuroso (Jayapangus Press, 2026)
Teachers’ pedagogical competence is a key factor in improving the quality of learning in primary schools. However, pedagogical competence is influenced by several factors, including the principal’s situational leadership style and teachers’ digital literacy. This study aims to analyze the effect of the principal’s situational leadership style and digital literacy, both partially and simultaneously, on teachers’ pedagogical competence in public primary schools in Kunduran District, Blora Regency. This research employed a quantitative approach with an ex post facto design. The population consisted of 301 teachers, with a sample of 172 teachers selected using proportional random sampling. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with t-test and F-test after meeting classical assumption tests. The results show that: (1) the principal’s situational leadership style has a positive and significant effect on teachers’ pedagogical competence with a contribution of 40.8%; (2) digital literacy has a positive and significant effect on teachers’ pedagogical competence with a contribution of 36.6%; and (3) simultaneously, the principal’s situational leadership style and digital literacy have a significant effect on teachers’ pedagogical competence with a contribution of 48.8%. These findings indicate that improving teachers’ pedagogical competence is influenced not only by leadership factors but also by teachers’ ability to utilize digital technology. In conclusion, strengthening adaptive school leadership and enhancing teachers’ digital literacy continuously are essential strategies to improve pedagogical competence and the quality of learning in primary schools.